Evaluation and Development Recommendations of Malang City Islamic Center Using Post-Occupancy Evaluation Approach - Dimas Bagus Tri Sutrisno; Erna Winansih; Imam Santoso (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The purpose of establishing Malang City Islamic Center was to serve the Islamic community in the East Malang area, where a majority of residents are Muslim, as indicated by the presence of many Islamic boarding schools (Pondok Pesantren) in the area. Malang City Islamic Center's building still stands today. To begin this research, several surveys of the building were conducted, and some interviews were conducted with its users. The result is that Malang City Islamic Center currently functions as the Public Order Agency (Polisi Pamong Praja) Office, which they call "Graha Purva Praja". However, the name "Islamic Center" is still used because the building includes a multipurpose hall that is available to the entire community of Malang City free of charge for various public purposes, not just religious ones. This research uses a Post-Occupancy Evaluation approach to obtain an assessment of this building from the user's perspective, drawing on user experience and intuition. At the beginning of this study, several data collections were conducted, indicating that, for future development, it is necessary to add features and refresh the appearance across architecture, interior design, and site planning.